Gaze behaviour differentiates elite from non-elite female soccer players: a 2D video projections exploratory study - Meira, Cassio M.; Cortes, Cintia O.; Corbetta, Daniela M.; Oliveira, Dalton L.; Rodrigues, Sergio T. [UNESP]; Silva, Bruno V. F.; Massa, Marcelo (Universidad Miguel Hernandez de Elche, 2022)
The present study explored visual strategies employed by female soccer players of high, medium, and low levels of expertise. We used eye-tracking technology to examine how skill-based differences related to gaze behavior in 30 participants (10 in each group) who were required to respond physically to film images projected on a screen using soccer skills (penalty kick, dribbling, pass reception, and defensive cover). Data were collected from search rate (visual fixations duration and number, and number of fixated areas), percentage of viewing time, and variability of pupil diameter. Analyses revealed that female elite players engaged in more visual fixations, directed gaze toward more relevant areas of the scene, and showed less variability of pupil diameter, compared to their non-elite counterparts. Our findings seem to corroborate prior research which compared participants with different levels of expertise while performing soccer skills.
Keywords: football; motor control; motor skill; visual perception; visual search; women